High-energy systems are underrepresented in global porewater studies of sandy beach aquifers - Gudrun Massmann; Janek Greskowiak; Julius Degenhardt; Bert Engelen; Moritz Holtappels; Rena Meyer; Mike Müller-Petke; Nils Moosdorf; Jutta Niggemann; Katharina Pahnke; Vincent Post; Anja Reckhardt; et al. (Estuarine, Coastal and Shelf Science, 2025)

Reactive transport modeling to reveal the impacts of beach morphodynamics, storm floods and seasonal groundwater recharge on the biogeochemistry of sandy subterranean estuaries - Stephan L. Seibert; Gudrun Massmann; Rena Meyer; Vincent E.A. Post; Janek Greskowiak (Advances in Water Resources, 2025)

Spatial and temporal dynamics of groundwater biogeochemistry in the deep subsurface of a high-energy beach - Anja Reckhardt; Rena Meyer; Stephan L. Seibert; Janek Greskowiak; Magali Roberts; Simone Brick; Grace Abarike; Kojo Amoako; Hannelore Waska; Kai Schwalfenberg; Iris Schmiedinger; Oliver Wurl; et al. (Marine Chemistry, 2024)

Impact of mineral reactions and surface complexation on the transport of dissolved species in a subterranean estuary: Application of a comprehensive reactive transport modeling approach - Stephan L. Seibert; Gudrun Massmann; Rena Meyer; Vincent E.A. Post; Janek Greskowiak (Advances in Water Resources, 2024)

Corrigendum: Molecular traits of dissolved organic matter in the subterranean estuary of a high-energy beach: indications of sources and sinks - Hannelore Waska; Heike Simon; Soeren Ahmerkamp; Janek Greskowiak; Janis Ahrens; Stephan L. Seibert; Kai Schwalfenberg; Oliver Zielinski; Thorsten Dittmar (Frontiers in Marine Science, 2023)

Redox-zoning in high-energy subterranean estuaries as a function of storm floods, temperatures, seasonal groundwater recharge and morphodynamics - Janek Greskowiak; Stephan L. Seibert; Vincent E.A. Post; Gudrun Massmann (Estuarine, Coastal and Shelf Science, 2023)

The DynaDeep observatory – a unique approach to study high-energy subterranean estuaries - Gudrun Massmann; Grace Abarike; Kojo Amoako; Felix Auer; Thomas H. Badewien; Cordula Berkenbrink; Michael Ernst Böttcher; Simone Brick; Iris Valeria Medina Cordova; Jairo Cueto; Thorsten Dittmar; Bert Engelen; et al. (Frontiers in Marine Science, 2023)
Subterranean estuaries are connective zones between inland aquifers and the open sea where terrestrial freshwater and circulating seawater mix and undergo major biogeochemical changes. They are biogeochemical reactors that modify groundwater chemistry prior to discharge into the sea. We propose that subterranean estuaries of high-energy beaches are particularly dynamic environments, where the effect of the dynamic boundary conditions propagates tens of meters into the subsurface, leading to strong spatio-temporal variability of geochemical conditions. We hypothesize that they form a unique habitat with an adapted microbial community unlike other typically more stable subsurface environments. So far, however, studies concerning subterranean estuaries of high-energy beaches have been rare and therefore their functioning, and their importance for coastal ecosystems, as well as for carbon, nutrient and trace element cycling, is little understood. We are addressing this knowledge gap within the interdisciplinary research project DynaDeep by studying the combined effect of surface (hydro- and morphodynamics) on subsurface processes (groundwater flow and transport, biogeochemical reactions, microbiology). A unique subterranean estuary observatory was established on the northern beach of the island of Spiekeroog facing the North Sea, serving as an exemplary high-energy research site and model system. It consists of fixed and permanent infrastructure such as a pole with measuring devices, multi-level groundwater wells and an electrode chain. This forms the base for autonomous measurements, regular repeated sampling, interdisciplinary field campaigns and experimental work, all of which are integrated via mathematical modelling to understand and quantify the functioning of the biogeochemical reactor. First results show that the DynaDeep observatory is collecting the intended spatially and temporally resolved morphological, sedimentological and biogeochemical data. Samples and data are further processed ex-situ and combined with experiments and modelling. Ultimately, DynaDeep aims at elucidating the global relevance of these common but overlooked environments.

Molecular Traits of Dissolved Organic Matter in the Subterranean Estuary of a High-Energy Beach: Indications of Sources and Sinks - Hannelore Waska; Heike Simon; Soeren Ahmerkamp; Janek Greskowiak; Janis Ahrens; Stephan L. Seibert; Kai Schwalfenberg; Oliver Zielinski; Thorsten Dittmar (Frontiers in Marine Science, 2021)
Advective flows of seawater and fresh groundwater through coastal aquifers form a unique ecohydrological interface, the subterranean estuary (STE). Here, freshly produced marine organic matter and oxygen mix with groundwater, which is low in oxygen and contains aged organic carbon (OC) from terrestrial sources. Along the groundwater flow paths, dissolved organic matter (DOM) is degraded and inorganic electron acceptors are successively used up. Because of the different DOM sources and ages, exact degradation pathways are often difficult to disentangle, especially in high-energy environments with dynamic changes in beach morphology, source composition, and hydraulic gradients. From a case study site on a barrier island in the German North Sea, we present detailed biogeochemical data from freshwater lens groundwater, seawater, and beach porewater samples collected over different seasons. The samples were analyzed for physico-chemistry (e.g., salinity, temperature, dissolved silicate), (reduced) electron acceptors (e.g., oxygen, nitrate, and iron), and dissolved organic carbon (DOC). DOM was isolated and molecularly characterized via soft-ionization ultra-high-resolution mass spectrometry, and molecular formulae were identified in each sample. We found that the islands’ freshwater lens harbors a surprisingly high DOM molecular diversity and heterogeneity, possibly due to patchy distributions of buried peat lenses. Furthermore, a comparison of DOM composition of the endmembers indicated that the Spiekeroog high-energy beach STE conveys chemically modified, terrestrial DOM from the inland freshwater lens to the coastal ocean. In the beach intertidal zone, porewater DOC concentrations, lability of DOM and oxygen concentrations, decreased while dissolved (reduced) iron and dissolved silicate concentrations increased. This observation is consistent with the assumption of a continuous degradation of labile DOM along a cross-shore gradient, even in this dynamic environment. Accordingly, molecular properties of DOM indicated enhanced degradation, and “humic-like” fluorescent DOM fraction increased along the flow paths, likely through accumulation of compounds less susceptible to microbial consumption. Our data indicate that the high-energy beach STE is likely a net sink of OC from the terrestrial and marine realm, and that barrier islands such as Spiekeroog may act as efficient “digestors” of organic matter.